2018
DOI: 10.1371/journal.pone.0203394
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic risk assessment of smartphone users using the Rapid Upper Limb Assessment (RULA) tool

Abstract: The number of smartphone users globally is rapidly increasing. This study aimed to assess the level of ergonomic risk to smartphone users, and to evaluate the correlation between any self-reported musculoskeletal disorders and the level of ergonomic risk. Thirty participants completed a questionnaire, tailored specifically for smartphone users, to determine any musculoskeletal disorders. Participants were given a seated smartphone texting task and their postures were video recorded during the task. The video s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 33 publications
3
35
0
5
Order By: Relevance
“…This hypothesis applies to muscles that are active for durations long enough to damage muscle fibers 7) . Namwongsa et al 50) revealed the three main risk factors responsible for upper-limb musculoskeletal disorders (i.e., posture, muscle force, and muscle use). Smartphone users commonly assume three poor postures, including protracting and bending the shoulders more than 20 degrees, setting elbows at more than 100 degrees and bending wrists more than 15 degrees with ulnar deviations, and forward neck and trunk flexion of 20 degrees or more.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis applies to muscles that are active for durations long enough to damage muscle fibers 7) . Namwongsa et al 50) revealed the three main risk factors responsible for upper-limb musculoskeletal disorders (i.e., posture, muscle force, and muscle use). Smartphone users commonly assume three poor postures, including protracting and bending the shoulders more than 20 degrees, setting elbows at more than 100 degrees and bending wrists more than 15 degrees with ulnar deviations, and forward neck and trunk flexion of 20 degrees or more.…”
Section: Discussionmentioning
confidence: 99%
“…In our digital world, increase smartphone usage has also led to psychological strain, ergonomic risks leading to musculoskeletal disorders, commonly neck pain (Namwongsa et al, 2018). Thus, musculoskeletal issues are at peak due to the drastic increase in the use of handheld devices like mobile phones, game controls, tablets, portable media players and personal digital assistants (Sharan et al, 2014).…”
Section: Musculoskeletal Issues Reported With the Use Of Smartphonesmentioning
confidence: 99%
“…RULA can be carried out quickly, allowing multiple positions and tasks within the work cycle to be evaluated with minimal time and effort. When using RULA, right and left limbs are assessed separately (Namwongsa, Puntumetakul, Neubert, Chaiklieng, & Boucaut, 2018 A video of two minutes is taken from a journey of one hour based on the driving deviation. The current study is focused primarily on evaluating this activity.…”
Section: Observational Studymentioning
confidence: 99%